DEVELOPING PERFORMANCE ASSESSMENT INSTRUMENT FOR MEASURING SCIENTIFIC ATTITUDES - Debi Shinta; Dadan Rosana (Jurnal Kependidikan, 2017)
This study was aimed at developing an instrument of performance assessment based on the 7E learning cycle model and finding out the result of students’ scientific attitude measurement using the instrument. The study was conducted by adapting the Borg and Gall research method. The subjects of this study were students of grade eight of State Junior High School 2 Binangun, Cilacap, Central Java. Data were obtained from:  first, experts’ judgements in determining the content validity of the instrument. Second, scores of the limited field try-out used in determining the reliability of the instrument, data collection instruments in the form of observation sheet, self assessment, and peer assessment. Third, students’ scientific attitudes in field try-out used to show the result of the measurement using the instrument. Findings show that the developed instrument of performance assessment is valid and reliable; and feasible to be used for measuring scientific attittudes, with measurement results in the good category equally for the three data collection instrumentsPENGEMBANGAN INSTRUMEN PENILAIAN KINERJAUNTUK MENGUKUR SIKAP ILMIAHPenelitian ini bertujuan untuk mengembangkan instrumen performance assessment berbasis model learning cycle 7E yang layak digunakan dan mengetahui hasil pengukuran sikap ilmiah menggunakan instrumen yang telah dikembangkan. Penelitian ini dikembangkan dengan adaptasi model Borg and Gall. Subjek uji coba yaitu peserta didik kelas VIII SMP Negeri 2 Binangun, Kabupaten Cilacap, Provinsi Jawa Tengah. Data dalam penelitian ini diperoleh melalui: pertama, penilaian berdasarkan masukan para ahli, untuk menentukan validitas isi instrumen. Kedua, hasil uji coba terbatas untuk menentukan reliabilitas instrumen, instrumen pengumpulan data berupa lembar observasi, penilaian diri, dan penilaian antarteman. Ketiga, data hasil sikap ilmiah peserta didik pada uji coba lapangan digunakan untuk mengetahui hasil pengukuran dengan instrumen yang telah dikembangkan. Instrumen performance assessment berbasis model learning cycle 7E yang dikembangkan dinyatakan valid dan reliabel sehingga layak digunakan serta terbukti dapat digunakan untuk mengukur sikap ilmiah peserta didik dengan hasil ukur pada kategori baik yang setara pada ketiga instrumen pengumpulan data